2011
DOI: 10.1007/s11548-011-0548-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of two 3-D fluoroscopic systems for articular fracture reduction: a cadaver study

Abstract: Intraoperative 3D fluoroscopes can detect clinically significant intra-articular step-off with acceptable measurement errors, using newer devices that enable the use of a conventional C-arm and reduced radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…41 Intraoperative imaging may reduce the need to return to the operating room to address articular malreductions and/or intra-articular hardware penetration missed on standard intraoperative fluoroscopy and later discovered on postoperative CT. Intraoperative imaging technology has progressed with the use of intraoperative CT, particularly for guided placement of pedicle screws in spine fusions; however, this is not standard practice for reduction of articular fractures.…”
Section: Assessment Of Articular Reductionmentioning
confidence: 99%
“…41 Intraoperative imaging may reduce the need to return to the operating room to address articular malreductions and/or intra-articular hardware penetration missed on standard intraoperative fluoroscopy and later discovered on postoperative CT. Intraoperative imaging technology has progressed with the use of intraoperative CT, particularly for guided placement of pedicle screws in spine fusions; however, this is not standard practice for reduction of articular fractures.…”
Section: Assessment Of Articular Reductionmentioning
confidence: 99%
“…Since its first application at the start of the 21st century, intraoperative 3D imaging has become increasingly important in the treatment of displaced intra-articular fractures [ 5 ]. Several cadaveric and clinical studies have verified that diagnostic accuracy, fracture reduction and implant position can be improved by using intraoperative 3D imaging in different anatomical regions [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic accuracy of 3D fluoroscopy appears to be higher than 2D fluoroscopy and similar to computed tomography (CT) for the evaluation of both reduction and implant position. 5 , 13 , 22 , 36 …”
mentioning
confidence: 99%
“…The diagnostic accuracy of 3D fluoroscopy appears to be higher than 2D fluoroscopy and similar to computed tomography (CT) for the evaluation of both reduction and implant position. 5,13,22,36 Three-dimensional fluoroscopy has proven to be a valuable addition to conventional intraoperative fluoroscopy in calcaneal fracture surgery. 16 Previous studies of 3D fluoroscopy in calcaneal fracture surgery have reported an intraoperative correction rate of up to 47% for indications that were not recognized on conventional 2D fluoroscopy.…”
mentioning
confidence: 99%